INVESTIGATION OF ENHANCEMENT FACTORS FOR THE USAGE OF MEDIATION IN MALAYSIAN CONSTRUCTION INDUSTRY. - Hussin, Siti Nurhayati; Ismail, Zulhabri (Journal of Technology Management and Business, 2015)
Disputes are inevitable elements in construction industry which must be solved within reasonable time; if not it may cause non compensable damages such as delays which may affect project performance. Thus, mediation as simple, rational, speedy and economical means of dispute resolution is needed. The practice of it has persistently being integrated as part of the construction industry; nevertheless the used of mediation is still at minimum level. This research aims to further enhance the use of mediation in Malaysian Construction Industry by way of proposing factors to further enhance the used of it. The objectives of the research are to explore the current development of mediation in Construction Industry; to determine the extent of mediation being used in the settlement of disputes as well as to identify factors to further enhance the use of mediation in Construction Industry. The research has adopted quantitative research method by way of questionnaire survey. The findings revealed that the current development of mediation in construction industry takes into place with the establishment of Alternative Disputes Resolution (ADR) institutions that related to mediation in Malaysia such as the Kuala Lumpur Regional Centre of Arbitration and Malaysian Mediation Centre (MMC), with functions to promote mediation as one of the options for the settlement of construction disputes under its rules and procedures. Continue with implementation in recent CIDB standard form of contract for building works edition 2000 and Agreement and conditions of PAM contract 2006. The enforcement of Mediation Act 2012 (Act 749) further develops and encourages toward active the implementation of mediation. Apart from that, various critical causes of dispute have been found and lack of registered mediation cases being observed due to perception that disputes become more complicated or even worse by participation of a third party. Thus, negotiation suggested as the most commonly method being used. Last but not least, raising awareness on advantages of mediation recommended as the most significant factors to further enhance the use of mediation by. To conclude, construction industry can benefit from the mediation approach. Thus, the industry as a whole must collaborate and improve the adoption of mediation in Malaysian construction industry.Â